Molecular Epidemiology of Rift Valley Fever Virus - Grobbelaar, Antoinette A.; Weyer, Jacqueline; Leman, Patricia A.; Kemp, Alan; Paweska, Janusz T.; Swanepoel, Robert (Emerging infectious diseases, 2011)
Phylogenetic relationships were examined for 198 Rift Valley fever virus isolates and 5 derived strains obtained from various sources in Saudi Arabia and 16 countries in Africa during a 67-year period (1944-2010). A maximum-likelihood tree prepared with sequence data for a 490-nt section of the Gn glycoprotein gene showed that 95 unique sequences sorted into 15 lineages. A 2010 isolate from a patient in South Africa potentially exposed to co-infection with live animal vaccine and wild virus was a reassortant. The potential influence of large-scale use of live animal vaccine on evolution of Rift Valley fever virus is discussed.